2022
DOI: 10.15282/ijame.14.3.2017.7.0354
|View full text |Cite
|
Sign up to set email alerts
|

Propeller shrouding influence on lift force of mini unmanned quadcopter

Abstract: This article discusses the lift force generated by a mini unmanned aerial vehicle. Shrouded propellers were considered and analyses of shroud influence on lift force and energy saving were done. By help of laboratory experiments and computational fluid dynamics simulations (propeller velocity varied from 1000 rpm to 6000 rpm, shroud height from 20 mm to 60 mm, gap from 3 mm to 28 mm), it was shown that the shroud diameter influenced the rotor energy consumption up to 30% at velocities of more than 4000 rpm. Wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Moaad, et al [26] reported that the improvement of drone maneuverability can be achieved by optimizing the ducted fan. Penkov, et al [27] examined the interactive impact on the lift force production on a mini UAV with the propellers shrouded in various shroud diameters and heights computationally and experimentally. Shukla, et al [28] conducted aeroacoustic measurements with a rotor with a removable protective duct over a range of hover conditions by means of stereo particle image velocimetry (SPIV).…”
Section: Aerodynamic Theory Of a Ducted Propellermentioning
confidence: 99%
See 2 more Smart Citations
“…Moaad, et al [26] reported that the improvement of drone maneuverability can be achieved by optimizing the ducted fan. Penkov, et al [27] examined the interactive impact on the lift force production on a mini UAV with the propellers shrouded in various shroud diameters and heights computationally and experimentally. Shukla, et al [28] conducted aeroacoustic measurements with a rotor with a removable protective duct over a range of hover conditions by means of stereo particle image velocimetry (SPIV).…”
Section: Aerodynamic Theory Of a Ducted Propellermentioning
confidence: 99%
“…Besides, the criterion of numerical convergence was set to be that either the maximum residual of pressure is less than 5 × 10 −5 or the maximum iteration steps is more than 3000. The CFD simulations were further validated via comparison of the lift force generated by the propeller with EXP data [27] under the same conditions, in terms of different diameters of the cylindrical shroud surrounding the propeller, from 270 mm to 310 mm with an interval of 10 mm, and a fixed shroud height of 60 mm (with the propeller having The CFD simulations were further validated via comparison of the lift force generated by the propeller with EXP data [27] under the same conditions, in terms of different diameters of the cylindrical shroud surrounding the propeller, from 270 mm to 310 mm with an interval of 10 mm, and a fixed shroud height of 60 mm (with the propeller having a radius of 127 mm and a rotational velocity of 5000 rpm). As shown in Figure 8, the CFD results are consistent with EXP results, sharing a similar trend that the propeller-induced lift force increases linearly with an increasing gap, while being lower than that of the non-ducted propeller accompanying a notable difference, which is caused by the different propeller morphology in the models of CFDs and EXPs.…”
Section: Verification and Validationmentioning
confidence: 99%
See 1 more Smart Citation
“…Rotorcraft such as helicopters [21,22] and quadcopters [23][24][25] have been improving for many years. The working principles of quadcopters in particular have been extensively described in literature, [26][27][28][29][30][31][32][33] with most attention related to balance control and stability. [26][27][28][29] A few detailed analyses exist which relate to calculation of thrust, but with different effective efficiency.…”
Section: Concise Model For Power Analysismentioning
confidence: 99%